Infectious endocarditis course after ascending aorta replacement with a valved conduit - N. A. Morova; V. N. Tsekhanovich (SINAPS LLC, 2019)
Objective. To demonstrate the peculiarities of infectious endocarditis course in patients after ascending aorta replacement using a valved conduit based on the personal observations.Material and methods. Six cases of delayed infectious endocarditis after ascending aorta replacement using a valved conduit are presented.Results. The pathological process was represented by aortic root abscess, paraprosthetic phlegmon, fistula penetrated into the conduit wall and cardiac chambers. There was no vegetation on the prosthesis therefore the diagnosis was complicated. Period from fever onset to final diagnosis lasted from 1 week to 2.5 months. The first pathologic changes in all cases were detected using transesophageal echocardiography, but this method was not informative in the early stages of the disease.Conclusion. Infectious endocarditis in patients after ascending aorta replacement using a valved conduit has its own peculiarities. The most frequently, the process leads to the development of aortic root abscess. Diagnosis of infectious endocarditis in such cases is difficult. Infectious endocarditis should be suspected in patients - carriers of valved conduit with unexplained fever and treatment should be started in accordance with the diagnosis. In this case, structural changes visualization to confirm the disease is not necessary.